2019
DOI: 10.1111/ans.15139
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of paediatric septic arthritis of the hip and knee at 1–20 years in an Australian urban centre

Abstract: Background: Septic arthritis in children is a joint threatening condition with potentially severe consequences; however, long-term outcome data is lacking. This study aims to determine 1-20-year outcomes following septic arthritis of hip and knee joints in children in an Australian population. Methods: All paediatric patients with septic arthritis of the hip or knee from 1995 to 2015 treated at our Australian institution were retrospectively assessed. Clinical features, treatment and investigation results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…First, we assessed objective outcomes by physical examination only. This is in contrast with other studies in which diagnostic imaging was performed (6,7,11,26). We were concerned that performing diagnostic imaging routinely as part of the followup study procedures would not be acceptable for many participants and lead to a selection bias in favor of those with ongoing complaints.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…First, we assessed objective outcomes by physical examination only. This is in contrast with other studies in which diagnostic imaging was performed (6,7,11,26). We were concerned that performing diagnostic imaging routinely as part of the followup study procedures would not be acceptable for many participants and lead to a selection bias in favor of those with ongoing complaints.…”
Section: Discussionmentioning
confidence: 96%
“…A Korean study including children with hip arthritis <18 months of age observed excellent or good clinical outcomes in 84% after a mean follow-up of 6 years (26). Another study in 52 Australian children with septic arthritis reported normal function with excellent outcomes assessed by radiographic imaging in 81% of those with hip and 100% of those with knee arthritis after a mean follow-up of 8.5 years (11). A further study from the United States of America, including 134 children with acute or subacute osteomyelitis, reported excellent or good outcomes with complete clinical resolution and minor radiological changes assessed in 92% after a follow-up of 2.5 years (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations